Just Business: A Framework for Developing Android Applications Using Naked Objects - Freitas, Fabiano; Maia, Paulo Henrique M. (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2015: Anais do IX Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2015)
Naked Objects is an architectural pattern in which the business objects are handled directly in the user interface. In this pattern, developers are responsible only for the creation of business classes and do not need to concern with the implementation of the other layers. Although used in several frameworks for making the development of web and desktop systems faster, there is still a lack of tools that add the benefits of that pattern to the creation of Android applications. This paper introduces Just Business, a Naked Objects-based framework, which aims at supporting fast creation of Android business applications through automatic code generation from mapping the business classes. A case study that describes how it was used and its evaluation is also provided.